Potencial evocado auditivo de tronco encefálico com estímulo iChirp-Narrow band por via óssea em neonatos e lactentes - Martins, Quemile Pribs (2023)
Bone conduction research in the auditory assessment of newborns and infants is important to define the type of hearing impairment, and is necessary whenever the auditory thresholds are altered. The frequency-specific Auditory Brainstem Response (fsABR) is the gold standard test for measuring electrophysiological thresholds in this population and the widely used stimulus is the Tone Burst. However, new stimuli have been demonstrating excellent responses by air conduction, such as the Chirp stimuli. Therefore, the general objective of the present study is to describe and compare different stimuli and at different intensities, by bone conduction, at a specific frequency in neonates and infants without hearing impairment. The sample of the present study consisted of 14 neonates, seven male and seven female. The research procedure was fsABR by bone conduction, at a frequency of 2000Hz, at intensities of 50 and 30 dBnHL, with Tone Burst and iChirp- narrow band (NB iChirp) Stimuli. Statistically significant differences were observed between the stimuli, with the Tone Burst stimulus presenting wave V earlier than the NB iChirp stimulus, and the NB iChirp stimulus producing greater wave V response amplitudes in ABR in neonates and infants. Furthermore, it was possible to present wave V latency and amplitude values with the NB iChirp, at the electrophysiological threshold at the specific frequency of 2000Hz, by bone conduction in the studied sample.